2010
DOI: 10.1002/nau.20871
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of bladder wall thickness is associated with the overactive bladder syndrome

Abstract: Mean BWT is associated with a symptom history of OAB and MUI, higher daytime and nightime frequency, and higher VAS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
(18 reference statements)
3
25
1
Order By: Relevance
“…Only OAB patients diagnosed based on their symptoms, and compared with normal healthy individuals. In the study by Panayi et al [15] whose study design was closest to ours, BWT values of patients with OAB symptoms were compared Median BWT measurements of the patients with stress, and mixed type incontinence based on International Continence Society criteria, and those of OAB syndrome were found to be 4.7, 5.4, and 5.6 mm, respectively. In our study, pre-, and post-voiding BWT measurements performed using transabdominal US examinations of the patients diagnosed as OAB were evaluated separately, and compared with those of normal healthy individuals without any urinary system complaints.…”
Section: Discussionmentioning
confidence: 96%
“…Only OAB patients diagnosed based on their symptoms, and compared with normal healthy individuals. In the study by Panayi et al [15] whose study design was closest to ours, BWT values of patients with OAB symptoms were compared Median BWT measurements of the patients with stress, and mixed type incontinence based on International Continence Society criteria, and those of OAB syndrome were found to be 4.7, 5.4, and 5.6 mm, respectively. In our study, pre-, and post-voiding BWT measurements performed using transabdominal US examinations of the patients diagnosed as OAB were evaluated separately, and compared with those of normal healthy individuals without any urinary system complaints.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, it was forwarded that BWT/DT could be influenced by the work overload of the bladder wall introduced by DO. Indeed, some authors have reported a trend of increasing DT associated with the severity of urgency as reported by Panayi and coworkers (Panayi et al, 2010). Khullar and co-workers analysed the total BWT via transvaginal ultrasound in a group of female patients with idiopathic DO (Khullar et al, 1996).…”
Section: Bladder Wall Thickness/detrusor Thickness (Bwt/dt)mentioning
confidence: 73%
“…If on a full bladder, then what should be the volume? The majority of facilities prefer an transvaginal procedure, but some practitioners advocate that these measurements be performed transperineally [27,28].…”
Section: Ultrasoundmentioning
confidence: 99%